MALONDIALDEHIDE (MDA) URINE AS AN EARLY MARKER OF DEVELOPMENTAL DISORDERS OF CHILDREN LIVING AROUND GOLD MINES - Ernawati; Adi Heru Sutomo; Indwiani Astuti; Enda Silvia Putri; Marniati; Itza Mulyani; Sufyan Anwar; Eva Flourentina Kusumawardani; Suci Eka Putri; Hasanuddin Husin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Children born to mothers living around gold mines are at risk of mercury exposure (Hg) and can cause developmental disorders. These developmental disorders can be detected early through stress oxidation mechanisms based on Hg toxicity that directly harm brain cells. It can be detected early on from the level of DNA damage, which is malondialdehyde (MDA) in the urine. Examining children's MDA urine levels near gold mines is the aim of this study. The Observational Research Method performs measurement of MDA of baby urine with TBARS examination of 16 babies in the age range of 2-14 weeks babies who live around the gold mining village Kalirejo Prefecture Kokap district of Kulon Progo Yogyakarta. The result was a rate of 3.23 μmol/L of MDA in baby urine, which is above the normal level of 1.03 μMol/L. So it can be concluded that the high level of MDI in the baby's urine is an early indication of a child's developmental disorder living around the gold mining.